Liner shipping industry : the impact of strategic alliance on financial perfomance / Balbino Juanito - Balbino, Juanito (Institute of Graduate Studies, UiTM, 2015)
Strategic alliance is one of the earliest forms of business alliances that emerged in modern history. It is formed to generate benefits that would otherwise not be easily achievable independently. The formation of strategic alliances has been seen as a response to globalization and growing uncertainty in the business environment. Through this collaboration, carriers have the opportunity to achieve economies of scale, increase sailing frequency, reduce cost and business risks, offer quality services, increased direct port calls, and a broader range of customer service options. In today’s highly competitive environment, it is a requirement for the shipping companies to provide low cost, high quality services to meet more demanding customer needs and respond to expanding world-wide markets...